Extracción de aceite a partir de semillas de sambo (cucurbita ficifolia) proveniente de la Parroquia Chuquiribamba del Cantón Loja - Guartanza Loja, José Luis (2023)
Sambo is a vegetable whose pulp is partially used, but the seeds, which have oleaginous properties, are discarded. These properties can be used for both edible and industrial purposes, such as oil extraction. For this reason, it is objetived to determine the optimum parameters for extracting oil from Sambo seeds using the mechanical method; to do end, five treatments were evaluated using different heating times of the equipment (expeller press); once the oil was obtained, it was centrifuged to eliminate all the impurities and thus obtain a quality oil; to determine the best treatment, the results of the performance were taken into account and then the quality of the oil was evaluated by physico-chemical analysis and also the production cost and selling price was determined. The results obtained show that the T3 treatment has the best extraction parameters, which consisted in heating the extraction press for about 15 minutes and centrifuging for 17 minutes at 4000 rpm since it obtained the highest extraction performance (29,65 %) and the best scores in the organoleptic analyses (odour, colour, and flavour). The results of the quality analysis were 9.01 mEq.O2 kg-1 peroxide value, 2.40% oleic acid for acidity level, 109.58 cg g-1 iodine value, and 189.84 mg KOH g-1 saponification value, which meet national and international standards for vegetable oils for the food industry. In addition, the production cost and the retail price of 250 ml of oil were USD 8.96 and USD 12.46 respectively. This research contributes to the development of farmers in the municipality of Chuquiribamba by providing a new alternative for value addition, waste reduction, and the creation of a new source of income. Keywords: sambo seeds, sambo oil, mechanical extraction, quality analysis, production costs.